Online Impulse Buying Analysis Reviewed From Shopping Lifestyle And Flash Sale Students Of Shopee Consumer UNPER - Rindayani, Neng Ririn; Askolani, Askolani; Arif, Arif (Multidisciplinary Journals, 2024)
The purpose of this study is to determine the influence of OnlineImpulse Buying Reviewed from Shopping Lifestyle and Flash Sale on Unper Shopee Consumer Students. The type of research used is quantitative, with a sampling technique, namely purposive sampling, with a total of 100 respondents. The data collection method in this study is a survey method using a questionnaire through a google form.The data analysis technique uses multiple linear regression through SPSS version 25. The results of the study showed that the variables of shopping lifestyle and sale flage had a partial and simultaneous effect on online impulse buying in students of the University of Struggle Shopee consumers.